High outcrossing rates in a self‐compatible and highly aggregated host‐generalist mistletoe. Issue 24 (19th October 2022) - Li, Manru; Sui, Yi; Wang, Xuanni; Ma, Zhanxia; Luo, Yahuang; Aluthwattha, Sasith Tharanga; McKey, Doyle; Pujol, Benoit; Chen, Jin; Zhang, Ling
Abstract: Plants have evolved various strategies to avoid inbreeding, but the mass flowering displayed by many plants predisposes them to within‐plant pollen movements and self‐pollination. Mistletoes often aggregate at multiple spatial scales. Their bird pollinators often visit several flowers of the same individual and of others on the same host tree. We hypothesized that hermaphroditic mistletoes have self‐incompatibility mechanisms that reduce or prevent selfing. Whether their spatial distribution, affected by host specificity, host distribution, and the behaviour of seed dispersers, influences their mating system and population genetic structure remains unclear. We studied how mating system and spatial distribution affect genetic structure in four populations of the host‐generalist mistletoe Dendrophthoe pentandra in southwestern China using microsatellite markers and progeny arrays. We also characterized the fine‐scale spatial genetic structure among 166 mistletoes from four host trees in one population. Prevalence and intensity of infection both appeared to vary among host species, strongly affecting the degree of aggregation. Host tree size had a strong effect on infection intensity. Surprisingly, manual pollination experiments indicated that D. pentandra is self‐compatible, but genetic analyses revealed that outcrossing rates were higher than expected in all four populations (MLTR t m 0.83–1.20, Bayesian t m 0.772–0.952). Spatial genetic structure was associated with distance between host trees but not at shorter scales (within hosts). Our results demonstrate that the combination of bird pollination, bird‐mediated seed dispersal, and post‐dispersal processes result in outcrossing and maintain relatively high diversity in the presence of biparental inbreeding, despite very high local densities and possible self‐compatibility.